The Development of an Automatic Environment Control System in Greenhouses for Phoenix Oyster Mushrooms using the Internet of Things - Phoriya, Pensiri; Chotisirimethanon, Sirichai; Ngamsanit, Piyarat; Thipprasert, Suda; Butwapee, Wirat (Journal of Applied Informatics and Technology, 2025)
Mushrooms are rich in protein, nutritional substances, and health-enhancing medicinal substances, making them a popular choice for consumption. This popularity has spurred a growing interest in mushroom cultivation. However, mushrooms thrive only within specific temperature and humidity ranges. Deviations from these conditions can adversely affect their growth and overall production. Therefore, this research aimed to develop an automatic environmental control system in greenhouses for Phoenix oyster mushrooms using the Internet of Things and evaluated the system's performance by experts while also assessing user satisfaction. The system is designed to control temperature and humidity to be at the optimum level for mushroom growth. It sends alerts to users if the temperature exceeds a specified threshold. The system utilizes NodeMCU to connect with temperature and humidity sensors and controls equipment such as water sprayers, ventilation fans, heat bulbs, and lights inside the greenhouse. Accessible via a web application, the system employs software development tools, including Arduino IDE, Firebase real-time database, LINE Notify, and Google Sheets. Statistical analysis relied on mean and standard deviation. The results showed that the system could effectively control greenhouse conditions to cultivate Phoenix oyster mushrooms through web applications and send LINE notifications. This may help reduce damage to Phoenix oyster mushroom cultivation that could occur. Evaluation results from experts scored were at the highest level, with an average of 4.79, while user satisfaction evaluations were also at the highest level, with an average score of 4.80.